Studi Kritik Hadis tentang Sedekah sebagai Jalan Menuju Kesejahteraan Umat - Hindy Asyfa; Ilim Abdul Halim; Dadang Darmawan (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about alms. This study uses an approach approach by applying the descriptive-analytical method. The object of this formal research is the science of hadith, while the material object is the hadith about alms to Muslims no. 1679. The results and discussion of this study indicate that the quality of the hadith regarding alms is considered authentic with the qualifications of maqbul ma'mul bih Islamic experience. This study concludes that the hadith narrated by Muslim No. 1679 is relevant as a motivation so that people have more welfare to hasten, because it is beneficial for the development of the ummah.